MD analysis of heat transfer of carbon nanotube flow on nanopumping process to improve the hydrodynamic and thermal performances. (November 2022) - Kou, Guiyue; Jahanbakhsh, Milad; Molaee, Mohammadali; Abbasi, Narges; Shahgholi, Mohamad; Inc, Mustafa
Abstract: A carbon nanotube (CNT) is a promising structure for nanoscale heat and mass transfer processes and targeted drug delivery (TDD). These appropriate behavior of CNTs cause this nanometric arrangement to be used in various clinical purposes, as drug delivery process. Here, we report nanopumping behavior of CNT sample in presence of an atomic defect and external heat flux (HF). Molecular Dynamics (MD) approach in this computational research consists of two main steps. In first step, equilibrium of defined compounds is described by Temperature (T) and Total Energy (TE) reporting. Results indicated that defined samples reach an equilibrium state after 1 ns. Next, nanopumping process is done by implementing external HF and metallic tips oscillating in vicinity of defected CNT as second step. Physical quantities such as T, TE, radial distribution function (RDF), nanopumping time, kinetic energy (KE), and Velocity (V)/T profiles of defined compounds were reported after two main processes were done. MD outputs indicated C20 molecule (target particle in nanopumping process) displaced inside CNT after 46.68 (ps), and by defining external flux, this time decreased to 43.12 (ps). Finally, we concluded that atomic defect and HF are important parameters that can be controlled nanopumping process in various clinical applications.